Perencanaan Manajemen Sumber Daya Manusia - Leonita Yani Larasati (STIKes Ibnu Sina Ajibarang, 2024)
HR planning is very important, considered as the first and most important part of HR management. This article details the theoretical basis of HR planning. The authors have attempted to provide a complete picture of these important human resource practices. This literature review discusses the importance of human resource planning, its objectives, and the influence of strategic factors. This research also includes human resource planning models and frameworks as well as explanations of how to retain and motivate company employees.